2005
DOI: 10.1002/pssa.200461503
|View full text |Cite
|
Sign up to set email alerts
|

Advanced characterization techniques of nonuniform indium distribution within InGaN/GaN heterostructures grown by MOCVD

Abstract: Nonuniform indium distribution within InGaN/GaN single quantum well (SQW) structures with nanoscale islands grown by metalorganic chemical vapor deposition (MOCVD) have been characterized by advanced characterization techniques. Robinson backscattered electron (BSE) measurements show cluster‐like BSE contrast of high brightness regions, which are not centered at small dark pits in a SQW structure of spiral growth mode. By comparing with the secondary electron (SE) images, the bright cluster areas from the BSE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
2
3
1
Order By: Relevance
“…This finding is consistent with the work of Lu et al [28], who also found a higher efficiency in PL measurements of spiral InGaN islands compared to a planar SQW LED structure. Different from the results of other groups [24,28], our CL measurements showed no dark spots of significant contrast, which could be attributed to non-radiative recombination centers, while surface sensitive methods like AFM and SEM point to a dislocation density of more than 1 Â10 9 cm À2 . Because of a spiral density of about 3 Â 10 7 cm À2 , a single spiral is centered at one single dislocation but statistically extends over 30 others.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with the work of Lu et al [28], who also found a higher efficiency in PL measurements of spiral InGaN islands compared to a planar SQW LED structure. Different from the results of other groups [24,28], our CL measurements showed no dark spots of significant contrast, which could be attributed to non-radiative recombination centers, while surface sensitive methods like AFM and SEM point to a dislocation density of more than 1 Â10 9 cm À2 . Because of a spiral density of about 3 Â 10 7 cm À2 , a single spiral is centered at one single dislocation but statistically extends over 30 others.…”
Section: Discussionsupporting
confidence: 93%
“…The increase of Ith for T AR ¼ 760 1C illustrates that Ith is strongly affected by the enhanced spiral growth resulting in spatial fluctuations of the luminescence. In contrast to a higher slope efficiency found in LED structures [28] and a reduced nonradiative recombination (see Fig. 5), we found that an enhanced spiral growth of the AR results in a reduced LD performance.…”
Section: Discussioncontrasting
confidence: 80%
“…One explanation could be indium accumulation in the center of the growth spirals, which was already found by Lu et al 12 using backscattered electron images. This accumulation is more pronounced at higher temperature.…”
Section: Resultsmentioning
confidence: 79%
“…1). 12 The spiral diameters were observed to be about 400 nm to 800 nm. The density of growth spirals was about 3 9 10 7 cm À2 and did not differ between samples grown at different temperatures.…”
Section: Resultsmentioning
confidence: 98%
“…More detailed descriptions of sample preparation, growth conditions, and growth parameters have been presented elsewhere. 9 All samples were cleaned with trichloroethylene, acetone, and methanol in an ultrasonic bath, followed by a rinse in isopropanol and then acid cleaning using HCl: H 2 O ͑1:1͒ prior to processing or imaging. Ohmic contacts were fabricated on all samples by deposition of 33 nm Ti/ 77 nm Al/ 33 nm Ti/ 88 nm Au followed by annealing at 650°C for 3 min.…”
Section: Methodsmentioning
confidence: 99%